Insomnia pada Lansia: Tantangan dalam Mendiagnosis dan Pemberian Perawatan - Fatma, Siti; Sunarti, Sri (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Age – related sleep changes are common symptoms in elderly and are related to various factors including physiologic factor, sleep habits, comorbid diseases, and also drug side effect. Screening for primary sleep disorder, comorbid diseases, and mental diseases such as depression and anxiety are essential. Managing insomnia is challenging because it may require comprehensive assessment to make precise diagnosis and also several treatment needed such as lifestyle changes, controlling comorbid disease, non pharmacological interventions as first line treatment, and then pharmacological interventions regarding efficacy, acceptability tolerability, and adverse events of the drugs.